The oppositional imagination : feminism, critique, and political theory - Cocks, Joan, 1947- (Routledge library editions. Feminist theory ;, 2012)
The Oppositional Imagination draws together elements from Marxism, analytical philosophy, post-structuralism, and post-colonial criticism to analyse the elusive interplay of culture and power. It focuses its attention on cultural domination, opposition and evasion in the realm of sex and gender. Joan Cocks reflects on questions crucial to both political theorists and feminists: the relationship between political theory and practical life; the possibility of bringing together a philosophical and a literary language to comprehend and evoke concrete experience; and the reconcili.